Scapular dyskinesis in elite boxers with neck disability and shoulder malfunction - Jung, J. W.; Kim, Y. K. (Medicina, 2021)
Background and Objectives: Neck and shoulder injuries commonly occur during boxing, and scapular dyskinesis is related to those injuries. This study investigated scapular dyskinesis with neck disability and shoulder malfunction in elite boxers. Materials and Methods: Seventy-two elite boxers participated in this study. Scapular dyskinesis was evaluated as normal, subtle, and obvious. Neck disability index (NDI), shoulder internal (IR), and external (ER) range of motion (ROM), isometric strength of IR and ER, and pectoralis minor length were measured and compared with the severity of scapular dyskinesis. Results: Thirty-eight boxers (52.7%) showed scapular dyskinesis. NDI score was significantly different (normal = 3.89 ± 3.08, obvious = 7.36 ± 4.95, p = 0.025). Isometric IR strength was significantly different (normal = 10.48 ± 2.86, obvious = 8.46 ± 1.74, p = 0.01). The length of the pectoralis minor was significantly different (normal = 10.17 ± 0.67, subtle = 9.87 ± 0.79, obvious = 9.47 ± 0.85; p = 0.001), and the dominant and non-dominant arm IR ROM was significantly different (dominant = 57.43 ± 11.98, non-dominant = 64.62 ± 10.3, p = 0.001). Conclusions: The prevalence of scapular dyskinesis is high among elite boxers. Boxers with scapular dyskinesis presented shoulder malfunction as well as neck disability. Further investigation is necessary to examine the relationship between scapular dyskinesis and neck disability in boxers